Dechema corrosion handbook : corrosive agents and their interaction with materials - Behrens, Dieter (Weinheim : VCH, 1987)
v.1. Acetates, aluminium chloride, chlorine and chlorinated water, fluorides, potassium hydroxide, steam, sulfonic acids -- v.2. Aliphatic aldehydes, ammonia and ammonium hydroxide, sodium hydroxide, soil (underground corrosion) -- v.3. Acid halides, amine salts, bromides, bromine carbonic acid, lithium hydroxide -- v.7. Aliphatic ketones, ammonium salts, atmosphere, potassium chloride -- v.9. Methanol, sulfur dioxide -- v.10. Carboxylic acid esters, drinking water, nitric acid -- v.11. Chlorine dioxide, seawater -- v.12. Chlorinated hydrocarbons, chloroethanes, phosphoric acid